2018
DOI: 10.1186/s12889-018-5726-9
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of yellow fever and related Flavi viruses in Ethiopia: a public health perspective

Abstract: BackgroundYellow fever (YF) is a viral hemorrhagic fever, endemic in the tropical forests of Africa and Central and South America. The disease is transmitted by mosquitoes infected with the yellow fever virus (YFV). Ethiopia was affected by the largest YF outbreak since the vaccination era during 1960–1962. The recent YF outbreak occurred in 2013 in Southern part of the country. The current survey of was carried out to determine the YF seroprevalence so as to make recommendations from YF prevention and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 7 publications
(9 reference statements)
5
31
2
Order By: Relevance
“…However, the observed overall sero-prevalence (49.5%) of IgG antibody against YFV was low compared to the results of other sero-prevalence studies conducted in YF vaccinated populations in Sudan [32], Brazil [33] and other country [34]. On the other hand, the sero-prevalence against YFV in our study was still higher than the national pooled sero-prevalence of Ethiopia [35] and Western Kenya [19]. These geographic based https://doi.org/10.1371/journal.pntd.0008549.g003…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 95%
See 1 more Smart Citation
“…However, the observed overall sero-prevalence (49.5%) of IgG antibody against YFV was low compared to the results of other sero-prevalence studies conducted in YF vaccinated populations in Sudan [32], Brazil [33] and other country [34]. On the other hand, the sero-prevalence against YFV in our study was still higher than the national pooled sero-prevalence of Ethiopia [35] and Western Kenya [19]. These geographic based https://doi.org/10.1371/journal.pntd.0008549.g003…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 95%
“…Previous studies in rural Kenya [20], Senegal [27], Tanzania [39], Bangladesh [40] and Singapore [25] reported a higher percentage of sero-prevalence of IgG antibody against many arboviruses including YFV in older individuals. Previous study in Ethiopia also showed a higher sero-prevalence of IgG antibody to YFV in individuals in the age category of 40-64 years [35]. A similar trend was also observed in the current study.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
“…Since YFV vaccination is an expected cause of cross-reactions, we performed PRNT for DENV and YFV in a subset of samples, and found that the congruence between DENV ELISA and PRNT was lower than in American and Asian settings (33)(34)(35)(36)(37). A similar observation was made in another study in DRC with a certain level of discordance between ELISA and PRNT (38), and in a study in Ethiopia where crossreaction and low confirmation by PRNT was also shown (39). In our study, the majority of the samples negative with DENV PRNT was also negative with PRNT for YFV, which indicates that the high flavivirus IgG positivity was not due to YFV vaccination.…”
Section: Resultssupporting
confidence: 67%
“…At the DAP‐HCFMUSP, after deparaffinisation and heat‐induced epitope retrieval, liver, kidney, pancreas, heart, spleen and testis sections were incubated for 18 h overnight with the primary antibody at 4°C. The primary antibody employed was a goat anti‐human immunoglobulin (Ig)M polyclonal anti‐YFV antigen provided by Institute Pasteur‐Dakar, originally standardised for enzyme‐linked immunosorbent assay (ELISA) and validated at the optimised dilution of 1:20 000 with positive and negative controls . Amplification of the reaction was achieved by the polymer molecules conjugated to peroxidase [Reveal – Biotin‐Free Polyvalent horseradish peroxidase diaminobenzidine (HRP DAB); Spring Bioscience, Pleasanton, CA, USA, code SPD‐125] and chromogen (Dako Liquid DAB (DAB) + substrate chromogen system; Dako, Carpenteria, CA, USA, code K3460).…”
Section: Methodsmentioning
confidence: 99%